Presence of Arcobacter spp. in environmental waters correlates with high levels of fecal pollution - Luis Collado; Isabel Inza; Josep Guarro; Maria Jose Figueras (Environmental Microbiology, 2008)
Summary We investigated the presence of Arcobacter spp. in 205 water samples of freshwater, seawater and sewage in Spain. These bacteria were present in 55.1% of the samples (113/205) and were significantly associated for the first time with bacterial indicators of fecal pollution. The dominant species in the positive samples was Arcobacter butzleri (94%) followed by Arcobacter cryaerophilus (30%) and Arcobacter skirrowii (1.8%).

The Southern Region of Peru Earthquake of June 23rd, 2001 - Hernando Tavera; Efraín Fernández; Isabel Bernal; Yanet Antayhua; Consuelo Agüero; Henry Salas Simeón Rodríguez; Luis Vilcapoma; Yolanda Zamudio; David Portugal; Adolfo Inza; Julia Carpio; Freddy Ccallo; et al. (Journal of Seismology, 2006)